▼Drotrecogin alfa (activated) for severe sepsis. Issue 1 (1st January 2006) - Unknown
Abstract : Sepsis, the systemic inflammatory response to infection, is common among severely ill patients and can be life-threatening. Over a quarter of patients in UK intensive care units (ICUs) have severe sepsis in the first 24 hours after admission.1 Of these, 35% die before leaving the ICU and 47% before leaving hospital despite standard therapy.1 ▼Drotrecogin alfa (activated) (Xigris - Eli Lilly), a recombinant human activated protein C, is licensed for treating adults who have severe sepsis with multiple organ failure. Here we assess its efficacy and safety.